2016
DOI: 10.1097/dcr.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Operative Method for Transverse Colon Carcinoma: Transverse Colectomy Versus Extended Colectomy

Abstract: In terms of perioperative and oncological outcomes, transverse colectomy and extended colectomy did not differ despite a shorter specimen length and fewer lymph nodes harvested in the transverse colectomy group. Independent prognostic factors for DFS were node-positive disease, the presence of vascular invasion, and ulcerative morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 26 publications
2
61
1
1
Order By: Relevance
“…According to Chong et al this is due to the possibility of these tumors giving rise to lymph-node metastases through both superior and inferior mesenteric vessels. Another reason for the poor survival rates could be the proximity to other organs which often requires a more aggressive surgery [9]. These are potential sources of complications after surgery and have led to the exclusion of transverse tumor cases in many large prospective randomized trials [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to Chong et al this is due to the possibility of these tumors giving rise to lymph-node metastases through both superior and inferior mesenteric vessels. Another reason for the poor survival rates could be the proximity to other organs which often requires a more aggressive surgery [9]. These are potential sources of complications after surgery and have led to the exclusion of transverse tumor cases in many large prospective randomized trials [10].…”
Section: Discussionmentioning
confidence: 99%
“…The inferior mesenteric vessels and the left branch of the middle colic vessels were ligated at their origins, and a regional lymphadenectomy was performed. Intestinal continuity was restored by a side-to-end mechanical colorectal anastomosis 9,17,18 .…”
Section: Methodsmentioning
confidence: 99%
“…At the best of our knowledge, only few studies investigated a segmental splenic flexure resection compared to extended colectomy, with the goal of proving the oncological equivalence between these two approaches. Moreover only the 14% of surgeons seem to perform segmental resection for splenic flexure cancer 6,911 .…”
Section: Introductionmentioning
confidence: 99%
“…Transverse colon cancer has a 5-year survival rates of 25-50% which is significantly poorer outcome compared with cancers in the other part of the colon [5] TC cancer has various number of technical description but lacks about indications of real gold standard technique. Due to the risk of vascular insufficiency and for the anatomical location in proximity of superior mesenteric artery and technical difficulties to splenic and hepatic flexure takedown, TC and EC are two challenging procedures.…”
Section: Discussionmentioning
confidence: 99%
“…TC had lower harvested lymph nodes (LNs) and small size of colon resection. Independent prognostic factors for DFS were node-positive disease, vascular invasion, and ulcerative morphology (Figures 2 and 3) [5]. Guan et al found inferior number of harvested nodes in transverse resection but similar rate of nodes positivity between transverse resection and EC.…”
mentioning
confidence: 95%